Extracellular matrix modulates T cell clearance of malignant cells in vitro. (March 2022) - Robertson, Claire; Sebastian, Aimy; Hinckley, Aubree; Rios-Arce, Naiomy D.; Hynes, William F.; Edwards, Skye A.; He, Wei; Hum, Nicholas R.; Wheeler, Elizabeth K.; Loots, Gabriela G.; Coleman, Matthew A.; Moya, Monica L.
Abstract: Despite the success of T cell checkpoint therapies, breast cancers rarely express these immunotherapy markers and are believed to be largely "immune cold" with limited inflammation and immune activation. The reason for this limited immune activation remains poorly understood. We sought to determine whether extracellular matrix substrate could contribute to this limited immune activation. Specifically, we asked whether extracellular matrix could alter T cell cytotoxicity against malignant mammary gland carcinoma cells (MCC) in a setup designed to promote maximal T cell efficacy (i.e., rich media with abundant IL2, high ratio of T cells to MCC). We observed that T cell clearance of MCC varied from 0% in collagen 4 or 6 conditions to almost 100% in fibronectin or vitronectin. Transcriptomics revealed that T cell function was defective in MCC/T cell cocultures on collagen 4 (Col4), potentially corresponding to greater expression of cytokines MCC cultured in this environment. In contrast, transcriptomics revealed an effective, exhausted phenotype on vitronectin. The observation that Col4 induces T cell suppression suggests that targeting tumor-ECM interactions may permit new approaches for utilizing immunotherapy in tumors which do not provoke a strong immune response. Graphical abstract: We studied clearance of malignant cells by strain mismatched T cells in a microenvironmental microarray. We observed a stark difference in clearance of malignant cells cultured in different environments, which we correlated to altered expression of T cell differentiation markers, chemokines and other immunosuppressive factors in different ECM conditions. Image 1